Karbon Biru pada Ekosistem Mangrove : Dinamika, Kapasitas Penyimpanan, dan Implikasinya terhadap Mitigasi Perubahan Iklim - Pahmi Husain; Muhammad Shohibul Ihsan; Raden Didi Kuswara; Khaerul Ihwan; Dwi Kartika Risfianty; Irna Il Sanuriza; Ishmah Humaidatul Aminah Zaim Alyaminy; Baiq Naili Dewi Atika (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The purpose of this study is to comprehensively examine the role of blue carbon in mangrove ecosystems, with an emphasis on the capacity and dynamics of carbon storage. This research is library research, with the PRISMA approach. Literature search is carried out systematically through several major scientific databases, namely Google Scholar, ScienceDirect, and SpringerLink. The literature selection process was carried out by referring to the principle of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The selection stage includes article identification through the database, initial screening by removing duplicate articles, relevance assessment based on titles and abstracts, and feasibility evaluation through full text review. Data analysis was carried out descriptive-quantitative through the narrative synthesis method. The results of the study show that the mangrove ecosystem is one of the main components of blue carbon with a very high carbon storage capacity, especially in sediment compartments that are stable in the long term. The dynamics of mangrove blue carbon are influenced by the interaction between biological, physical, and chemical processes, such as vegetation productivity, litter accumulation, and sediment trapping by mangrove root systems. The carbon storage capacity of mangrove ecosystems varies between regions and is influenced by biotic and abiotic factors, including species composition, age and stand density, hydrological conditions, and substrate type. In addition to serving as carbon sinks and stores, mangrove ecosystems have strategic implications in climate change mitigation as nature-based solutions. However, the degradation and conversion of mangrove land have the potential to release stored carbon into the atmosphere and reduce mitigation capacity in the future. So that the conservation and sustainable management of mangroves is an important step in maintaining the function of blue carbon and supporting climate change mitigation efforts.